Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1111/jth.14751
|View full text |Cite
|
Sign up to set email alerts
|

Whole blood thrombin generation profiles of patients with cirrhosis explored with a near patient assay

Abstract: Background and Aims Patients with cirrhosis have a rebalanced hemostasis, often with normal or elevated thrombin‐generating (TG) capacity in plasma. Whole blood (WB) TG allows faster determination and, importantly, includes the influence of all circulating blood cells. We aimed to study the TG profile of patients with cirrhosis in WB and in platelet poor plasma. Methods Thrombin‐generating capacity in WB and plasma were assessed with a near‐patient WB‐TG assay and the calibrated automated thrombinography assay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 47 publications
1
26
0
1
Order By: Relevance
“… 14 Although a hemostatic balance is reached in cirrhosis, this equilibrium is more fragile and can easily lead to a hypo- or hyper-coagulable state. 15 In recent years, it has been evident that appropriately assessing patients for the risk of bleeding and thrombosis cannot be done with standard coagulation tests, such as PT, INR or APTT. 5 As our study showed, many cirrhotic patients develop PVT despite elevated PT, INR and APTT.…”
Section: Discussionmentioning
confidence: 99%
“… 14 Although a hemostatic balance is reached in cirrhosis, this equilibrium is more fragile and can easily lead to a hypo- or hyper-coagulable state. 15 In recent years, it has been evident that appropriately assessing patients for the risk of bleeding and thrombosis cannot be done with standard coagulation tests, such as PT, INR or APTT. 5 As our study showed, many cirrhotic patients develop PVT despite elevated PT, INR and APTT.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we recently showed that erythrocytes augmented peak thrombin level even in the presence of high platelet count (87). Furthermore, both in a group of healthy adults (87) and cirrhotic patients (112) we observed a positive correlation between hematocrit and the peak of WB-TG, indicating that erythrocytes have a positive effect on the velocity of WB-TG.…”
Section: Accepted Manuscriptmentioning
confidence: 56%
“…26,39 In vitro and ex vivo studies have demonstrated little to no prohemostatic effect of FFP by thrombin generation tests in patients with cirrhosis. 25,40 Although prophylactic administration of FFP in 43,44 In addition, it is unknown which level of ETP represents the optimal pro-or anticoagulant status; therefore, we do not have ETP target levels for management of thrombosis or bleeding. To incorporate dose adjustments in further studies, we would need such information to be able to adjust the dosing of pro-or anticoagulants in this specific population.…”
Section: Discussionmentioning
confidence: 99%
“…Thrombin generation is thus far only used in a research setting. It is a relatively cumbersome test and not yet ready for clinical use, although the automated test (Genesia) has been launched and whole blood thrombin generation tests that may be suitable as a point‐of‐care test are in development 43,44 . In addition, it is unknown which level of ETP represents the optimal pro‐ or anticoagulant status; therefore, we do not have ETP target levels for management of thrombosis or bleeding.…”
Section: Discussionmentioning
confidence: 99%